RANCANG BANGUN APLIKASI SIBAMA BERBASIS ANDROID MENGGUNAKAN PUSH NOTIFICATION PADA WARUNG AFFAN - Lestari Widayanti; Tri Hidayati (CV. Multi Kreasi Media, 2023)
Along with the development of technology that is already very advanced, the business of buying and selling food is becoming a trend in all circles. This can be seen from the number of social media accounts that sell food online and offline. The location of the seller who is sometimes far from the buyer's residence makes it difficult for the buyer to buy it. Related to the development of technology and the business of buying and selling food that is currently trending, the Sibama Application is made which is the sale and purchase of basic food items such as: cooking oil, noodles, eggs and so on. Which aims to make it easier for buyers to get the desired basic needs efficiently and effectively. This Sibama application uses the Waterfall method with Push Notification, making it easier for sellers to receive notifications when a buyer enters. With this Push Notification, it can provide user convenience in the form of information. The way this system works is like a short message or a short message when a message comes in, a notification will appear to tell you about a message that has been sent or when the user's screen is run even if the user opens the application or not. The results obtained from the Sibama application research can help someone in obtaining groceries online easily using only a cellphone and more time efficient.